LITERATURE REVIEW : TANTANGAN SERTA SOLUSI PENYANDANG DISABILITAS UNTUK MENDAPATKAN PERLINDUNGAN PEMENUHAN HAK PEKERJAAN - Haniifa Mawarningsih; Hastin Trustisari (JOURNAL SAINS STUDENT RESEARCH, 2024)
People with disabilities often face challenges in gaining equal access to employment opportunities. Limited access and infrastructure, discrimination, and lack of education and skills are the main obstacles. This article aims to provide equal access to education and skills training, create an inclusive work environment, and implement policies that support quotas for workers with disabilities and equal access to infrastructure and technology. This assessment method uses literature studies with online narrative types on Google Scholar. Conclusion: The importance of cross-sector collaboration to create an inclusive and fair work environment for all individuals, including people with disabilities. So that their rights to get work can be protected and fulfilled optimally in the future. It is hoped that these suggestions can create an inclusive and fair work environment for all individuals, including people with disabilities, so that their rights to obtain work can be protected and fulfilled